mTOR acts as a pivotal signaling hub for neural crest cells during craniofacial development. - Xuguang Nie; Jinxuan Zheng; Christopher L Ricupero; Ling He; Kai Jiao; Kai Jiao; Jeremy J Mao (PLoS Genetics)
mTOR is a highly conserved serine/threonine protein kinase that is critical for diverse cellular processes in both developmental and physiological settings. mTOR interacts with a set of molecules including Raptor and Rictor to form two distinct functional complexes, namely the mTORC1 and mTORC2. Here, we used novel genetic models to investigate functions of the mTOR pathway for cranial neural crest cells (NCCs), which are a temporary type of cells arising from the ectoderm layer and migrate to the pharyngeal arches participating craniofacial development. mTOR deletion elicited a proliferation deficit and excessive apoptosis of post-migratory NCCs, leading to growth arrest of the facial primordia along with midline orofacial clefts. Furthermore, NCC differentiation was impaired. Thus, NCC derivatives, such as skeletons, vasculatures and neural tissues were either rudimentary or malformed. We further demonstrate that disruption of mTOR caused P53 hyperactivity and cell cycle arrest in cranial NCCs, and lowering P53 activity by one copy reduction attenuated the severity of craniofacial phenotype in NCC-mTOR knockout mice. Remarkably, NCC-Rptor disruption caused a spectrum of defects mirroring that of the NCC-mTOR deletion, whereas NCC-Rictor disruption only caused a mild craniofacial phenotype compared to the mTOR and Rptor conditional knockout models. Altogether, our data demonstrate that mTOR functions mediated by mTORC1 are indispensable for multiple processes of NCC development including proliferation, survival, and differentiation during craniofacial morphogenesis and organogenesis, and P53 hyperactivity in part accounts for the defective craniofacial development in NCC-mTOR knockout mice.